Mindfulness as a Buffer of Leaders’ Self-Rated Behavioral Responses to Emotional Exhaustion: A Dual Process Model of Self-Regulation - Walsh, Megan M.; Arnold, Kara A. (Frontiers in Psychology, 2018)
In this study we use dual process theory of self-regulation to develop a framework that outlines the mediating and moderating mechanisms explaining the relationship between leader emotional exhaustion and leadership style (transformational leadership and abusive supervision). Using Glomb et al.’s (2011) framework, we identify empathy and negative emotion as mediators that are of particular importance for leaders. In addition, we propose that leader mindfulness moderates these processes to improve leadership style. Using a time-lagged survey of leaders (N = 505) we found that leader empathy and negative emotion mediated the relationships between emotional exhaustion and leadership style. Furthermore, we found that leader mindfulness significantly moderated the indirect effect of leader emotional exhaustion on leadership style through negative emotion. However, leader mindfulness did not moderate the relationship between emotional exhaustion and empathy. Theoretical and practical implications are discussed.